Microstructure of starch-based meals with either palm or soybean oils alter in vitro starch digestibility with no major effects on glycaemic responses. (3rd July 2020) - Bravo, Carolina; Santos, José L.; Castillo, Gabriel; Olivares, Gabriela; Parada, Javier
Abstract: Glycaemic response (GR) to starch-based meals depends on their food composition and microstructure. We studied the effect of palm and soybean oils on the microstructure of a solid starch-oil-gluten matrix, on the starch gelatinisation and in vitro digestibility. Additionally, a pilot cross-over study was carried out to assess GR after eating gelatinised starch/gluten-based foods with the addition of either palm or soybean oil in 8 young non-diabetic female volunteers (ISRCTN39636850). Both types of foods generated similar starch gelatinisation temperature. Starch/gluten-based food with soybean oil had rougher microstructure compared to food with palm oil, showing a higher initial and lower final in vitro digestion. Administration of starch/gluten-based meals with either palm or soybean oils to volunteers show very similar postprandial glucose or insulin responses. In conclusion, differences in fatty acid composition changes food microstructure and in vitro starch digestibility, with no major effects on glycaemic responses in female volunteers.